Investigating Students Attitudes on Oral Corrective Feedback: Small-scale Survey in Academic Speaking Class - Muti'ah; Maulidia Azizah, Vanya (Universitas Veteran Bangun Nusantara, 2024)
Due to the essentiality of oral presentation, giving corrective feedback was gaining potential discussion, especially in oral language. Thus, this study investigates the attitudes of graduate students within the English department at a Central Java, Indonesia university towards teachers' oral corrective feedback (OCF) during academic speaking presentations. Utilizing quantitative descriptive survey design, a 6-item questionnaire developed by Ur (1999) was administered using probability sampling on (n=23). This research explores preferences among students regarding explicit and implicit OCF, peer criticism, and meta-linguistic feedback. Results indicate a predominant preference (73.9%) for explicit OCF, reflecting a strong tendency toward direct and honest correction from teachers. While implicit OCF obtained positive responses, students exhibited reluctance towards peer criticism, expressing a preference for teacher feedback. However, there was notable enthusiasm (69.6%) for meta-linguistic OCF, highlighting students' receptiveness to linguistic nuances and novel perspectives. These findings underscore the significance of understanding students' preferences in OCF contexts, emphasizing the value placed on explicit teacher correction and the appreciation for meta-linguistic insights within academic speaking classes.